Characterization of mortars from the medieval Abbey of Cerrate (southern Italy). (April 2017) - Conte, Aida Maria; Corda, Laura; Esposito, Daniela; Giorgi, Elisabetta
Abstract: Mortars from the walls of S. Maria di Cerrate Abbey (South Italy) ranging in age from the 12th to the 20th century, were studied using a multidisciplinary approach designed to produce a guideline of investigation that can be applied to the knowledge and preservation of archaeological sites. The analyses highlighted the differences between medieval and post-medieval mortars; the former showed a dominantly carbonate aggregate, the latter a mostly siliciclastic aggregate. Among these, mortars dated from the XVI–XVII centuries display a mixed siliciclastic-carbonate binder whereas mortars from the XIX–XX centuries exhibit a predominantly carbonate binder with the Al-silicates mostly gathered as lumps. Highlights: Mortars from S. Maria di Cerrate complex (Salento, Italy) From the 12th to the 20th century masonry Multi-disciplinary study Historical-technical and mineralogical-petrographical characterization Comparison and distinction between mortars of different age